Factors influence tourist satisfaction in visiting Kota Kinabalu Sabah / Mohd Hamizi Abd Hamid and Khaleeda Maizura Kalimin - Abd Hamid, Mohd Hamizi; Kalimin, Khaleeda Maizura (Faculty of Business and Management, 2014)
The title of this research is “Factors Influence Tourist Satisfaction in Visiting Kota Kinabalu Sabah. This paper aims to identify factors that influence tourist satisfaction in visiting Kota Kinabalu Sabah. There are three independent variable involved in this research which are novelty, knowledge and facilities. In order to completing this research, the hypothesis was been constructed and focused on the objective to determine whether there has significant relationship between that independent variable with tourist satisfaction. A total of 150 tourists have participated in this study as respondent. The methodology used for this research was primary data collection and secondary data. For primary data, the researcher was used questionnaire to obtained and collect information. Thus, the result was been obtained through the analyzing and interpret data of result. The reliability test, frequency analysis, descriptive testing and Pearson’s correlation coefficient testing was used for data analysis. From the correlation testing, the result shows three independent variables have a moderate relationship with tourist satisfaction. For hypothesis, there are clearly shown that three hypothesis which including novelty, knowledge and facilities is supported.